2009
DOI: 10.1155/2009/384718
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Tetrahydrofolate Reductase and Angiotensin Converting Enzyme Gene Polymorphisms Related to Overweight/Obesity among Saudi Subjects from Qassim Region

Abstract: Abstract.Background: This work was planned to check for the association of polymorphisms related to methylenetetrahydrofolate reductase (MTHFR) and angiotensin converting enzyme (ACE) genes with overweight/obesity among Saudi subjects from Qassim region. Methods: This work included 130 subjects having overweight or obesity and 111 normal controls. Their age mean ± SD was 27 ± 9.8 and 24 ± 8.8 years respectively. Their DNA was analyzed for polymorphisms of MTHFR; 677C/T and 1298 A/C and ACE; I/D genes using rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…Associations between ACE I/D and obesity parameters show the same controversy regarding the risk allele. For instance, in the study of Bienertova-Vasku et al (2009), the II-genotype was found associated with the prevalence of obesity, whereas Settin et al (2009) reported a significantly higher BMI in D-allele carriers. It has also been shown that subjects with the D/D genotype lose less body fat with similar amounts of weight loss than I-allele carriers (Hamada et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Associations between ACE I/D and obesity parameters show the same controversy regarding the risk allele. For instance, in the study of Bienertova-Vasku et al (2009), the II-genotype was found associated with the prevalence of obesity, whereas Settin et al (2009) reported a significantly higher BMI in D-allele carriers. It has also been shown that subjects with the D/D genotype lose less body fat with similar amounts of weight loss than I-allele carriers (Hamada et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…There are conflicting results showing associations of MTHFR polymorphism and overweight or obesity (23)(24)(25). Some studies did not show such relations (23,24). However, some of them showed higher BMi and waist-to-hip ratio in healthy postmenopausal women being carriers of the 677C>T polymorphism compared to women with the CC genotype (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, statistically higher levels of serum HCys were found in the overweight or obese individuals compared to subjects with normal BMi (22). There are conflicting results showing associations of MTHFR polymorphism and overweight or obesity (23)(24)(25). Some studies did not show such relations (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…28 Finally, comorbidities, gender, and ethnic background may affect the results. For example, one study by Settin et al 8 showed that there was no marked association between ACE I/D gene polymorphism and noncomplicated overweight/obesity risk, and two studies 5,20 demonstrated that the association between ACE I/D gene polymorphism and overweight/obesity risk was gender dependent. All these prove at least the existence of other factors affecting the role of ACE I/D gene polymorphism in the onset of overweight/obesity, which offers an insight into investigating the association between ACE I/D gene polymorphism and overweight/obesity risk in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we included 12 studies 8,[10][11][12][13][14][15][17][18][19][20][21] in the sensitivity analysis.…”
Section: Sensitivity Analysismentioning
confidence: 99%